Building the Next Generation of Thai-Chinese: The Role of Chinese-Sponsored Schools in Hat Yai - Cummings, Jr., Robert L. (The Journal of the Siam Society, 2016)
This article exams the role of Chinese-sponsored schools in Hat Yai, Thailand in passing a Chinese cultural heritage on to the younger generations of the Thai-Chinese community. Three schools, Srinakorn Foundation, Kobkarnsuksa Foundation, and Khunnatham Wittaya, serve as key institutions for binding the ethnic Chinese community together, for teaching succeeding generations Chinese traditions, language and culture, as well as for connecting the community to a network of other ethnic Chinese communities. Evidence from interviews, questionnaires, and observation indicate that Thai-Chinese students are positively influenced by the Chinese-sponsored schools and value the Chinese elements of their blended Thai-Chinese community culture.